Assessing the suitability of sterile insect technique applied to Aedes aegypti - Ferreira, Claudia Pio [UNESP]; Yang, Hyun Mo; Esteva, Lourdes (World Scientific Publishing, 2008)
The efficacy of biological control of Aedes aegypti mosquitoes using Sterile Insect Technique (SIT) is analyzed. This approach has shown to be very efficient on agricultural plagues and has become an alternative control strategy to the usual technique of insecticide application, which promotes resistance against chemical controls and is harmful to other species that live in the same mosquito habitat. By using a discrete cellular automata approach we have shown that in the case of Aedes aegypti, the spatially heterogeneous distribution of oviposition containers and the mosquito behavior, especially with respect to mating, make the application of STI difficult or impracticable. © 2008 World Scientific Publishing Company.
Keywords: Aedes aegypti; Biological control; Cellular automata; STI technique